Normalization of the Haemostatic Plugs of Dogs with Haemophilia A (Factor VIII Deficiency) Following the Infusion of a Combination of Factor Xa and Phosphatidylcholine/Phosphatidylserine Vesicles - Ni, Hong yu; Giles, Alan R (Thrombosis and Haemostasis, 1992)
The bolus intravenous infusion of factor Xa in combination with phosphatidylcholine/phosphatidylserine (PCPS) vesicles, at a dose of 2.6 × 10-11 moles and 4.0 × 10-8 moles/kg body weight respectively, has previously been shown to correct the bleeding diathesis of haemophilic (factor VIII deficient) dogs (Br J Haematol 1988; 69: 491-7). The cuticle bleeding time (CBT) was used as the test to evaluate objectively this response. Transmission electron microscopy was performed to document the evolution of haemostatic plugs forming in the vascular bed of the injured cuticles of both normal and factor VIII deficient dogs with and without treatment with factor Xa/PCPS. The dosage previously shown to normalize the CBT in haemophilic and significantly shorten it in normal animals was used. Subjective and objective observations, using morphometric techniques, were made over a period of 25 min following injury induction. The administration of factor Xa/PCPS was associated with complete and sustained normalization of haemostatic plug development in the haemophiliacs including platelet recruitment, activation and compaction and subsequently fibrinous transformation. In the case of the normals, platelet activation, etc., was exaggerated and fibrinous transformation appeared to be accelerated. The haemostatic plugs forming in the treated haemophiliacs were indistinguishable from those forming in the normals and significantly different, with regard to all parameters measured, from the morphological appearances noted in the untreated haemophiliacs. These data suggest that the correction of the haemostatic defect previously observed results from the normalization of haemostatic plug formation and that this is sustained despite the promotion of systemic fibrinolysis that is also known to occur.